Artisanal fishermen from the estuary of the Timbó River, state of Pernambuco, Brazil: culture, survival and imaginary - Sassi, Roberto; Cabral, Adilson Luiz; Costa, Cristiane Francisca (SITIENTIBUS série Ciências Biológicas, 2007)
Some socio-cultural aspects of the fishermen community which lives and works in the estuary of the Timbó River, Pernambuco State, Brazil were studied during 1999, aiming at understanding how the estuarine resources are exploited by fishermen and also what are their daily practices and costumes. Data were obtained through semi-structured formularies and open interviews carried out with 150 local fishermen during several visits to the area. Database included aspects of the fishery activity, ethnomedicine, additional strategies they use for survival, and also aspects of the people’s imaginary. A great diversity of fishing devices is used by the fishermen, and its majority was created by themselves. Fishing is their main means of sustenance, but additionally several fishermen also raise farm animals and farm the land. Usually their diseases are dealt with natural products obtained in the estuary and surroundings, and its imaginary oscillates between the divine beliefs and the enchantment represented by a great amount of folk entities. These data could be useful for conservation purposes of the goods and services of this ecosystem and its biodiversity. They are also important for the perpetuation of proper local socio-cultural values, which are nowadays under strong pressure by several exogenous components.